Neurophysiological Findings in Neuronal Ceroid Lipofuscinoses - Trivisano, Marina; Ferretti, Alessandro; Calabrese, Costanza; Pietrafusa, Nicola; Piscitello, Ludovica; Carfi' Pavia, Giusy; Vigevano, Federico; Specchio, Nicola (Frontiers in Neurology, 2022)
Neuronal ceroid lipofuscinoses (NCLs) are a heterogeneous group of neurodegenerative diseases, characterized by progressive cerebral atrophy due to lysosomal storage disorder. Common clinical features include epileptic seizures, progressive cognitive and motor decline, and visual failure, which occur over different time courses according to subtypes. During the latest years, many advances have been done in the field of targeted treatments and in the next future, gene therapies and enzyme replacement treatments may be available for several NCLs variants. Considering that in NCLs there is rapid disease progression, early diagnosis is crucial and neurophysiological features might have a key role for this purpose. Across the different subtypes of NCLs, Electroencephalogram (EEG) is characterized by a progressive deterioration of cerebral activity with slowing of background activity and disappearance of spindles during sleep. Some types of heterogeneous abnormalities, diffuse or focal, prevalent over temporal and occipital regions, are described in many NCLs variants. Photo-paroxysmal response to low-frequency Intermittent Photic Stimulation (IPS) is a typical EEG finding, mostly described in CLN2, CLN5 and CLN6 diseases. Visual Evoked Potentials (VEPs) allow to monitor the visual functions and the lack of response at Electroretinogram (ERG) reflects retinal neurodegeneration. Taken together, EEG, VEPs, and ERG, may represent essential tools toward an early diagnosis of NCLs.